The Development of Pop Direction in European Countries and the Entry of Uzbekistan into the Art World. - Shomuradov Anvar Islomovich (Zien Journals, 2022)
This article covers the history and stages of development of pop music on the topic "Development of pop music in European countries and the entry of Uzbekistan into the world of art."
Keywords: Variety; genre; music hall; variety